Designing Human-Machine-Interface to Promote Eco-Driving Behavior - Zhao, Ziyi (My University, 2023)
As the demand for goods continues to grow in transportation, there has been an increasing focus on utilizing technologies in vehicles to mitigate the environmental impact of transport. One eco-friendly practice is promoting eco-driving behaviors among drivers, and the need for such effective onboard systems arises, leading to the investigation of human-vehicle interactions in both academia and industry. Aimed at safe, effective, and pervasive human-machine-interfaces (HMIs) to support ecodriving behavior, this project followed a research-through-design approach and an iterative design process. This project contributes to a set of design guidelines formalized from the practice of prototyping user interfaces for the onboard Driver Eco Coaching system in trucks, in support of future HMI design for eco-driving systems.
Keywords: eco-driving; human-machine-interfaces; human-vehicle-interaction; persuasive design; sustainable transportation; value-sensitive design